Natural fiber-reinforced composites using Miswak and Kenaf for sustainable food packaging - Shafi, Ayu Rafiqah; Rani, Mohd Saiful Asmal; Shahrizal, Muhammad Dany Haikal Eddy; Saleh, Muhammad Amir Fakrurazzi; Ali, Mohd Radzi; Abdan, Khalina (Taylor and Francis, 2026)
This study investigates poly(lactic acid) (PLA) hybrid composites reinforced with miswak fiber (MF) and kenaf fiber (KF) and evaluates how fiber ratio affects performance for food-packaging applications. MF and KF were alkali treated to reduce lignin and hemicellulose, then incorporated into a constant 70% PLA matrix. Composite sheets were fabricated by two-stage hydraulic hot pressing with fiber formulations of 30% KF, 20% KF + 10% MF, 10% KF + 20% MF, and 30% MF. The 10% KF + 20% MF hybrid exhibited the best mechanical properties (tensile strength 51 MPa, tensile modulus 6340 MPa, flexural strength 79 MPa, and flexural modulus 5650 MPa), exceeding common thresholds for packaging materials. The results indicate that an optimal MF/KF balance improves fiber–matrix interfacial adhesion and load transfer. Thermogravimetric analysis showed an onset degradation temperature of ~ 305°C, about 15°C higher than PLA reinforced solely with kenaf fiber (~290°C). The improved thermal stability is attributed to MF’s higher lignin content and enhanced interfacial bonding. Overall, MF/KF–PLA hybrids are promising bio-based alternatives to conventional packaging plastics.